Tender the Maker - Hutchins, Christina, 1961- (Book collections on Project MUSE., 2015)
"Hutchin's poems startle us into awareness of the overlooked, the nearly-always invisible, and the marvelous, those aspects of life that come under the rubric of 'mystery, ' in all sense of the word. Hutchins combines a pitch-perfect and precise lyricism with a postmodern sensibility of language's materiality"--